Characterization of exosomal release in bovine endometrial intercaruncular stromal cells. Issue 1 (December 2016) - Koh, Yong; Peiris, Hassendrini; Vaswani, Kanchan; Reed, Sarah; Rice, Gregory; Salomon, Carlos; Mitchell, Murray
Abstract Background Cell-to-cell communication between the blastocyst and endometrium is critical for implantation. In recent years, evidence has emerged from studies in humans and several other animal species that exosomes are secreted from the endometrium and trophoblast cells and may play an important role in cell-to-cell communication maternal-fetal interface during early pregnancy. Exosomes are stable extracellular lipid bilayer vesicles that encapsulate proteins, miRNAs, and mRNAs, with the ability to deliver their cargo to near and distant sites, altering cellular function(s). Furthermore, the exosomal cargo can be altered in response to environmental cues (e.g. hypoxia). The current study aims to develop an in vitro system to evaluate maternal-embryo interactions via exosomes (and exosomal cargo) produced by bovine endometrial stromal cells (ICAR) using hypoxia as a known stimulus associated with the release of exosomes and alterations to biological responses (e.g. cell proliferation). Methods ICAR cells cultured under 8 % O2 or 1 % O2 for 48 h and changes in cell function (i.e. migration, proliferation and apoptosis) were evaluated. Exosome release was determined following the isolation (via differential centrifugation) and characterization of exosomes from ICAR cell-conditioned media. Exosomal proteomic content was evaluated by mass spectrometry. Results Under hypoxic conditions (i.e. 1 % O2 ), ICAR cell migration and proliferation was decreased (~20 and ~32 %, respectively) and apoptotic protein caspase-3 activation was increased (∼1.6 fold). Hypoxia increased exosome number by ~3.6 fold compared with culture at 8 % O2 . Mass spectrometry analysis identified 128 proteins unique to exosomes of ICAR cultured at 1 % O2 compared with only 46 proteins unique to those of ICAR cultured at 8 % O2 . Differential production of proteins associated with specific biological processes and molecular functions were identified, most notably ADAM10, pantetheinase and kininogen 2. Conclusions In summary, we have shown that a stimulus such as hypoxia can alter both the cellular function and exosome release of ICAR cells. Alterations to exosome release and exosomal content in response to stimuli may play a crucial role in maternal-fetal crosstalk and could also affect placental development.